Pengaruh Penambahan Dedak Padi dengan Fermentasi Probiotik EM4 terhadap Peningkatan Populasi Daphnia magna - Daeng, Widiawati; Hasim, Hasim; Lamadi, Arafik (The NIKe Journal, 2023)
This research aims to determine the effect of adding organic rice bran material through the EM4 (Effective Microorganism) probiotic fermentation process with different doses on increasing the Daphnia magna population. This research was carried out from June to July 2018, which took place at the UPTD Multipurpose Entrepreneur Fish Seed Center, Gorontalo City. This research used the Experimental Method with a Completely Randomized Design (CRD) for three treatments and three replications, namely treatment A (5gr rice bran + 1 ml of fermented EM4), treatment B (5gr of fermented rice bran + 3 ml of fermented EM4), treatment C (5gr rice bran + EM4 5 ml fermented). The results of this research show that organic rice bran fermented using EM4 probiotics has an effect on Daphnia magna population growth. The research results showed that the best value was in treatment A, fermented rice bran produced the highest peak population on the eighth day with a density of 171 individuals/liter.